F+4/6g=6g

Simple and best practice solution for F+4/6g=6g equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for F+4/6g=6g equation:



+4/6F=6F
We move all terms to the left:
+4/6F-(6F)=0
Domain of the equation: 6F!=0
F!=0/6
F!=0
F∈R
We add all the numbers together, and all the variables
-6F+4/6F=0
We multiply all the terms by the denominator
-6F*6F+4=0
Wy multiply elements
-36F^2+4=0
a = -36; b = 0; c = +4;
Δ = b2-4ac
Δ = 02-4·(-36)·4
Δ = 576
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$F_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$F_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

$\sqrt{\Delta}=\sqrt{576}=24$
$F_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(0)-24}{2*-36}=\frac{-24}{-72} =1/3 $
$F_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(0)+24}{2*-36}=\frac{24}{-72} =-1/3 $

See similar equations:

| 5(+1)=2p+11 | | |x+17|+10=70 | | 6+7v+3v=v+8v | | a−12.9=29.4 | | 5/p=15/7 | | x/7-20=-10 | | 8m+3-m=19 | | -4x-9=5x+10x+10 | | 95+x+x=180 | | -41+7+2n=1 | | P^2-13=-12p | | 2z+5(z-1)=3z-1 | | 16x-13x-2x+2=7 | | 1/2(4x+8)=-1/2(-6x-12) | | 3a+1=-3.6(a-10) | | 6p–4+12p=-20+16p | | 15=13-x | | 2+2x=6x-2 | | 2.27x-0.27x+0.6=11.0 | | x2+2x+5=0 | | 6+2(3j-2)=4(1+j | | 5f-41=3f-9 | | .05X+.1X+.25x=2 | | -3n+-4n-5=0 | | 4x²+6x=0 | | 5x-15=20- | | .5X+.1X+.25x=2 | | 2y^2+3y=27 | | −2(7+2k)=3k | | -5m=100 | | -15n*18n+-4n-5=0 | | 2x^2+17x=-8 |

Equations solver categories